When Context Begins Affecting “Ziji” Anaphora Processing? Evidence from Semantic Priming - Zhang, Shiqian; Zhang, Delu (Neuroscience and Biomedical Engineering (Discontinued), 2017)
Background: Principle A of the Government and Binding Theory (Norm Chomsky, 1981, 1986) prescribes that a reflexive should refer to the local (short-distance) antecedent within the local syntactic domain. However, the Chinese bare reflexive “ziji” does not accord with Principle A. “Ziji” can refer to a local or long-distance antecedent, directly determined by context (co-text). Objective: The present study aims to explore when context begins affecting “ziji” anaphora processing. Methods: Using the semantic priming technique, we examined the nature of the earliest stage of context- manipulated “ziji” anaphora processing. Results: A priming effect on target words under (semantically) relevant contexts was detected; we also found the priming effect on the L-target under the long-distance contextual condition, but found no priming effect on the relevant target (the S-target) under the local (short-distance) contextual condition. Conclusion: The present study suggests that contextual information begins affecting “ziji” anaphora at its earliest processing stage; that is, context immediately affects “ziji” anaphora processing once it is available. However, at the earliest processing stage, the activation of contextual information is still asymmetric or inadequate.
Keywords: Anaphora